Evaluating the Impact of Vertical Greenery System on Cooling Effect on High Rise Buildings and Surroundings: A Review - Jaafar, Badrulzaman; Said, Ismail; Rasidi, Mohd Hisyam (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2011)
Rapid urbanization and the concern for climate change have led to a growing trend to bring nature into the cities. Due to artificial urbanization, urban heat islands have become a serious problem. Greenery is expected to be an effective countermeasure, and much research is available regarding green roofs, green walls, street trees and parks. The intent of this paper is to present a synthesis of the literature review on the design and technology for cooling of building and surroundings by using vertical greenery system. Effect of design parameters on building microclimate and the applicable cooling technologies are discussed.Keywords: Vertical greenery system, cooling effect, temperature reduction, humidity